Crocodile Skin‐Inspired Protective Composite Textiles with Pattern‐Controllable Soft‐Rigid Unified Structures (Adv. Funct. Mater. 12/2023). (16th March 2023) - Mao, Lizhou; Zhou, Mengjuan; Yao, Lu; Yu, Hang; Yan, Xuefeng; Shen, Yue; Chen, Wenshuai; Ma, Pibo; Ma, Yan; Zhang, Songlin; Tan, Swee Ching
Abstract : Soft‐Rigid Unified Structure Textile In article number 2213419, Swee Ching Tan, Songlin Zhang, Yan Ma, and co‐workers developed a composite textile with a soft‐rigid unified structure (SRUS) design inspired by crocodile skin. The SRUS textile combines excellent protective properties and wearing comfort, providing a new approach to personal protective equipment development. The study shows the potential of biomimetic design in creating innovative functional textiles.